A randomized, cross-over study to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of milvexian with single and dual antiplatelet therapy in healthy participants. (3rd October 2022) - Perera, V; Abelian, G; Luettgen, J; Aronson, R; Li, D; Wang, Z; Zhang, L; Lubin, S; Merali, S; Murthy, B
Abstract: Background: According to scientific evidence, modulation of Factor XI (FXI) function may provide a novel mechanism for systemic anticoagulation without increasing the risk of clinically relevant bleeding in a variety of conditions associated with a high risk of thrombotic events. Milvexian (BMS-986177/JNJ-70033093) is an oral small molecule that binds reversibly to and inhibits the active form of FXI (FXIa) with high affinity and selectivity. Depending on the patient population, milvexian is expected to provide benefit to patients as replacement or add on therapy to current guideline-recommended antithrombotic agents which include aspirin and/or clopidogrel. Purpose: This DDI study aimed to investigate the safety and to identify possible pharmacokinetic (PK) or pharmacodynamic (PD) interaction of milvexian when co-administered with aspirin and/or clopidogrel. Methods: The study consisted of 3 parts, each of which was a single DDI study using a randomized, 3-period, 3-treatment crossover design. Six unique treatment sequences were utilized in the study. Milvexian was placebo controlled and blinded when co-administered with aspirin and clopidogrel (Part 1), with clopidogrel (Part 2), or with aspirin (Part 3). In each case the subjects crossed over to milvexian monotherapy. Subjects were randomly assigned into 1 part of the study only. Results: Overall, multiple dose milvexian 200 mg given BID for 5 days with and without dual antiplatelet therapy (clopidogrel given as 300 mg on Day 1 followed by 4 days of 75 mg clopidogrel, and aspirin 325 mg once daily given for 5 days) was safe and well tolerated. There were 8 mild bleeding adverse events (AEs) reported from 5 subjects in various treatment groups; no trend towards increased bleeding potential was observed when milvexian was co-administered with dual antiplatelet therapy or separately with aspirin or clopidogrel. After co-administration of aspirin and clopidogrel with milvexian, peak (Cmax) and total exposure [AUC(TAU)] of milvexian were reduced 17% and 15%, respectively, on Day, 1 but were not changed on Day 5, compared to milvexian administered alone. After co-administration of clopidogrel or aspirin separately with milvexian, peak and total exposures of milvexian were not changed, compared to milvexian administered alone. Exposure-dependent prolongation of activated partial thromboplastin time (aPTT) and reduction of Factor XI clotting activity (FXIc) were observed with milvexian administration. Effects were similar when milvexian was administered alone or in combination with aspirin and/or clopidogrel. Conclusion: This Phase 1 study in healthy adults demonstrated administration of milvexian alone or in combination with aspirin and/or clopidogrel was not associated with a trend towards AE's including bleeding. Milvexian steady-state exposure and PD effects were similar when milvexian was administered alone or in combination with aspirin and/or clopidogrel. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bristol Myers Squibb and Janssen Pharmaceuticals